Prevention and Control of COVID-19 Infection in a Chinese Mental Health Center - Yang, Mi; Wang, Hongming; Li, Zhi; Zhang, Qiang; Liu, Xin; He, Manxi; Gao, Shan (Frontiers in Medicine, 2020)
Faced with the rapid spread of the novel coronavirus disease (COVID-19), a global public health threat, psychiatric hospitals are under huge pressure for preventing and controlling nosocomial infection. The current research analyzed the COVID-19 infection control practices in a regional mental health center in China and addressed how this type of medical institutions could enhance their ability to prevent and control hospital transmission of major respiratory diseases and general management of nosocomial infection risks. Firstly, hospital-related risks of COVID-19 were analyzed and then targeted prevention and control measures were established. Pre- and post-intervention theoretical knowledge of nosocomial infection control, hand hygiene compliance and accuracy, use of personal protective equipment, and disinfection and sterilization effectiveness were evaluated and compared. All the indexes displayed significant improvements following the implementation of the prevention and control measures. Up to the submission of this paper, the mental health center obtained no suspected or confirmed case of COVID-19 infection due to hospital transmission. The findings provide empirical evidence for the effectiveness of the COVID-19 preventive strategies and have important implications for integrated and characterized infection control in mental health centers during a major epidemic. Establishment of the transitional isolation ward and air fumigation using traditional Chinese medicine for patients and staff are preventive measures worthy of further discussion and diffusion.